RELATIONSHIPS OF CAUSAL ATTRIBUTIONS AND ACADEMIC ATTAINMENT AMONG COLLEGES OF EDUCATION STUDENTS IN NORTH- WESTERN NIGERIA - Sambo, A.; Balarabe, M.; Mohammed, A. (Sokoto Educational Review, 2018)
This study investigated the relationship of causal attributions and academic attainment of Colleges of Education students in north- west geo- political zone of Nigeria. The study was based on the hypothesis that there is no significant relationship between causal attributions and academic attainment of students. The questionnaire on Academic Causal Attribution Scale (ACAS) were administered to 389 students (300 level) drawn from eight (8) Colleges o f Education. Furthermore, students’ Grade Point Average (GPA) was used as measures of academic attainment. Thus, Pearson Product Moment Correlation was employed to determine the degree of relationship of the said variables. Thus, the findings revealed that there were no significant correlations identified among the causal attribution factors and academic attainment of students except with external attribution of failure in which significant correlation was established with academic attainment. The study therefore, recommends that students should not be reprimanded when they fail examination, instead, they should be encouraged to put more efforts and they should be involved in teaching and learning activities in a bid to encourage them so that they will record success in their future academic pursuit and as well minimize shifting blame for their failure consistently to external factors.